Modelling of the lubricant-layer thickness on a madrel during rolling seamless tubings - Ćurčija, Dušan (Materiali in tehnologije, 2013)
AutoCAD-a 3D modelling and the programs of Mathematica, MATLAB and MathCAD Professional were used to calculate the approximate solutions of the Reynolds differential equations for lubrication. Excel Software and Monte-Carlo solutions are compared. The results indicate a fast decrease in the lubricant-layer thickness in the stands for the continuous rolling of tubes. At the start of the rolling, the conditions for stable hydrodynamic lubrication are fulfilled for the tube-diameter-reduction processes. Theoretical calculations indicate that, on the finishing stands, "lubricant pickling" may occur on the mandrel. An approximate calculation is performed for the rolling point M and verified with the numerical Monte-Carlo method.
Keywords: toplotna obdelava; brezšivne cevi; Reynoldsova enačba; mazanje; valjanje